Clinical Outcome and Patient Satisfaction of Unipolar Radial Head Replacement: A longitudinal study - Thapa, Santosh; Shrestha, Oshan; Rajthala, Ashish; Jha, Ranjib Kumar (Birat Journal of Health Sciences, 2025)
Introduction: Excision of the radial head was frequently indicated in the past, as the radial head was considered to have a minimal role in the stability and biomechanics of the elbow. Now, it has been established that the radial head has an important role, and its removal has shown to alter the stability and biomechanics, due to which surgeons are motivated to preserve or replace the radial head during fracture management. Objectives: This study aims to study the short-term clinical outcome and patient satisfaction of radial head replacement with prosthesis. Methodology: This study was conducted among patients who underwent radial head arthroplasty. A study tool was prepared for data collection, and the data was refined in Excel and analyzed using SPSS 20. Outcomes were assessed by using different parameters like range of motion, mayo elbow performance score, time to return to work, patient satisfaction, and complications. Results: This study had sixteen participants with a mean age of 40.19 ± 11.391 and a male-to-female ratio of 3:1. Mayo Elbow Performance Scores (MEPS) had a median (IQR) score of 85 (80-96.25). The median for extension was 5°, for flexion was 140°, and for both pronation and supination was 80°. The median time taken for return to work was two months, and 12.5% of the patients reported being dissatisfied. Conclusion: Radial head arthroplasty preserves the elbow stability and reestablishes normal functioning of the elbow after radial head fracture Mason type III.